Physicochemical properties and glucose-lowering effect of an insulin - Aloe vera buccal delivery system - Chin, Heng Huay; Rehman, Khurram; Ng, Pei-Yuen; Mohd Hanif Zulfakar, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Subcutaneous insulin injection is one of the therapies in the treatment of diabetes mellitus. However, problems such as pain at the injection site and lipodystrophy present a challenge that will influence patient compliance. This study aims to develop and characterise buccal film formulations containing insulin, utilising the glucose-lowering and pharmaceutical properties of Aloe vera. Characterisation tests such as morphology, rheological measurement, pH value, mechanical properties, and permeation test were performed on the optimal formulation. Assessment of the glucose-lowering efficacy was performed using alloxan-induced diabetic rabbits. Composition of the final film formulation included 3% w/w sodium carboxymethyl cellulose, 40% v/v glycerol, 70% v/v Aloe vera, 0.5% w/v mannitol, 0.125% w/v aspartame, 0.125% v/v Tween 80 and 15.3 mg insulin. The drug content has been determined to be 56.77 ± 8.55%. The formulation shows a low variation in weight and thickness measurements and acceptable physicochemical properties, in addition to sustained drug release for 6 h. The final film formulation that combined insulin and Aloe vera was effective enough to reduce blood glucose levels compared to the negative control (p > 0.05), despite fluctuation in the blood glucose levels throughout the study, and did not show any enhancement in reduction compared to the insulin-only film. In conclusion, the developed buccal film formulation has the potential to be used as a vessel for the delivery of insulin. Nevertheless, further studies are required to ensure the stability of the insulin via buccal route and stabilisation of insulin within the formulation.